2017
DOI: 10.21109/kesmas.v12i1.1469
|View full text |Cite
|
Sign up to set email alerts
|

Level of Exposure of Childhood Tuberculosis with Adult Pulmonary Tuberculosis Household Contacts

Abstract: Pulmonary tuberculosis (TB) in children is a neglected global health problem, with an increasing proportion of TB cases in Indonesia. Children with TB are most often impacted by TB transmission in the population at large, especially adult TB that exists in the child's household. This study aimed to find protective factors that can keep children healthy despite household adult TB contacts. This study reports on 132 respondents with a case-control study conducted at nine referred hospitals and several primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Dede's research [11]states that people who live in unhealthy homes have a 2,152 times chance to suffer from pulmonary TB compared to those who live in healthy homes. Likewise with the results of al Asyary et al [12]study which states that a healthy home is able to protect children despite staying long with adults with tuberculosis. The results of this study are expected to be input for the health center in improving the degree of public health in their working area.…”
Section: Introductionsupporting
confidence: 57%
“…Dede's research [11]states that people who live in unhealthy homes have a 2,152 times chance to suffer from pulmonary TB compared to those who live in healthy homes. Likewise with the results of al Asyary et al [12]study which states that a healthy home is able to protect children despite staying long with adults with tuberculosis. The results of this study are expected to be input for the health center in improving the degree of public health in their working area.…”
Section: Introductionsupporting
confidence: 57%
“…Poor sunlight exposure activates influenza (Sagripanti and Lytle, 2007). Previous studies have shown that sunlight exposure significantly contributed to the healing of most respiratory conditions including tuberculosis and lung disease (Aloia and Li-Ng, 2007;Asyary et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found similar outcomes, i.e. that densely populated suburban and residential areas constitute neighbourhoods where TB is not only located but also concentrated (Asyary et al, 2017a).…”
Section: Discussionmentioning
confidence: 72%